2014
DOI: 10.1186/1471-2458-14-13
|View full text |Cite
|
Sign up to set email alerts
|

A study of the dietary intake of Cypriot children and adolescents aged 6–18 years and the association of mother’s educational status and children’s weight status on adherence to nutritional recommendations

Abstract: BackgroundA balanced diet is fundamental for healthy growth and development of children. The aim of this study was to document and evaluate the dietary intake of Cypriot children aged 6–18 years (y) against recommendations, and to determine whether maternal education and children’s weight status are associated with adherence to recommendations.MethodsThe dietary intake of a random sample of 1414 Cypriot children was assessed using a 3-day food diary. Adherence to recommendations was estimated and the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 50 publications
(62 reference statements)
5
17
1
8
Order By: Relevance
“…Our results are in line with a previous study conducted in Cyprus in children and adolescents where 62.8% of subjects were also shown to have normal weight [8]. Moreover Savva et al [9] indicated that the prevalence of obesity (8.1%) and overweight (20.1%) in children and adolescents in Cyprus has increased substantially over a decade, mainly in rural areas and in school-aged boys.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in line with a previous study conducted in Cyprus in children and adolescents where 62.8% of subjects were also shown to have normal weight [8]. Moreover Savva et al [9] indicated that the prevalence of obesity (8.1%) and overweight (20.1%) in children and adolescents in Cyprus has increased substantially over a decade, mainly in rural areas and in school-aged boys.…”
Section: Discussionsupporting
confidence: 92%
“…As PAL data were not available from the survey, we assigned a standard PAL of 1·55 to all respondents as per the advice of the Australian Bureau of Statistics (20) and similar to previous studies (27)(28)(29) . Participants with an energy intake:BMR ratio outside the 95 % CI were excluded from the analysis.…”
Section: Data Cleaningmentioning
confidence: 99%
“…The Goldberg cut-off (30) for 2-d dietary data and a physical activity level of 1.55 (i.e., plausible if the energy intake:basal metabolic rate ratio is within 0.96-2.49) was used to identify misreporters as previously described (31). This range was used per the advice of the Australian Bureau of Statistics (18), and is similar to that used in previous studies (32)(33)(34). We excluded 1093 extreme misreporters based on this method.…”
Section: Sensitivity Analysesmentioning
confidence: 99%